Single-pot synthesis of biodiesel using efficient sulfonated-derived tea waste-heterogeneous catalyst - Rashid, Umer; Ahmad, Junaid; Ibrahim, Mohd Lokman; Nisar, Jan; Hanif, Muhammad Asif; Choong, Thomas Shean Yaw (MDPI, 2019)
The main purpose of this manuscript is to report the new usage of tea waste (TW) as a catalyst for efficient conversion of palm fatty acid distillate (PFAD) to biodiesel. In this work, we investigate the potential of tea waste char as a catalyst for biodiesel production before and after sulfonation. The activated sulfonated tea waste char catalyst was characterized using Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), X-ray diffractometry (XRD), elemental composition (CHNS), nitrogen adsorption-desorption using Brunauer-Emmett-Teller (BET) and ammonia-temperature-programmed desorption (NH3-TPD). The activated tea waste char catalyst shows higher acid density of 31 μmol g−1 as compared to tea waste char of 16 μmol g−1 and higher surface area of 122 m2/g. The optimum fatty acid conversion conditions were found that 4 wt % of catalyst loading with 9:1 of methanol:PFAD for 90 min of reaction time at 65 °C gives 97% free fatty acid (FFA) conversion. In conclusion, the sulfonated tea waste (STW) catalyst showed an impressive catalytic activity towards the esterification of PFAD at optimum reaction conditions with significant recyclability in five successive cycles without any reactivation step.